Dynamic performance of dielectric elastomers utilized as acoustic actuators - Hochradel, Klaus; Rupitsch, Stefan; Sutor, Alexander; Lerch, Reinhard; Vu, Duc Khoi; Steinmann, Paul (Applied Physics A-Materials Science & Processing, 2012)
We report on the frequency dependent behavior of dielectric elastomer actuators (DEA). The introduced smart material actuators consist of 3M™'s elastomer VHB™4905 (9469) and a compliant, sputtered copper electrode on each side. The presented experiments on these compounds contain the active tuning of their resonance frequency and their application as acoustic actuators.We are able to decrease the membranes' eigenfrequency by 30% with an electrical offset potential. Alternatively, if an alternating signal is applied, sound pressure levels up to 130 dB in an enclosed volume of 28 ccm are achieved. In order to verify the results, a numerical simulation is introduced incorporating the two physical fields involved: electrical and mechanical. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-14:Pub.2012.tech.FT.FT-TM.dynami